The Relationship Between Online Gaming Habits with Carpal Tunnel Syndrome Among High School Students in Jakarta - Zethira, Andini Tania; Hendrati, Lucia Yovita (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
The Indonesian online gaming industry is growing rapidly. The increasing number of online game players among teenagers can cause various health impacts, one of them being carpal tunnel syndrome. This research aims to determine the relationship between online gaming habits with carpal tunnel syndrome in high school students in Jakarta. This research is an observational study with a cross-sectional design and a total of 62 samples. Questionnaires used in data collection include  playing habits, respondent knowledge, and the Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ). The collected data was analyzed using the Chi-Square test. The results showed  a relationship between playing duration (p=0.042), playing frequency (p=0.026), and repetitive movements (p=0.026) with complaints of Carpal Tunnel Syndrome. On the other hand, there was no significant relationship between gender (p=0.523), game type (p=1.00), gaming device (p=0.287), and knowledge (p=0.744) with complaints of Carpal Tunnel Syndrome. It would be better if the school provided further education to students and parents about the dangers of prolonged game duration and reminded them to regulate game-playing hours for students to avoid complaints of Carpal Tunnel Syndrome. Keywords: Carpal tunnel syndrome, online game, playing time, repetitive movements, students